2014
DOI: 10.1016/j.crohns.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and extraintestinal cancers in patients with primary sclerosing cholangitis and inflammatory bowel disease

Abstract: Introduction: Primary sclerosing cholangitis (PSC) and inflammatory bowel disease (IBD) frequently co-occur. PSC is associated with increased risk for colorectal cancer (CRC). However, whether PSC is associated with increased risk of extraintestinal cancers or affects mortality in an IBD cohort has not been examined previously. Methods: In a multi-institutional IBD cohort of IBD, we established a diagnosis of PSC using a novel algorithm incorporating narrative and codified data with high positive and negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 44 publications
(53 reference statements)
4
48
0
Order By: Relevance
“…In a previous study from our group, we confirmed the high positive predictive value of this diagnostic code in our EMR, consistent with published literature 24, 2628 . Our main predictor of interest was undergoing a colonoscopy within 36 months prior to the first date of CRC diagnosis (for cases) or end of follow-up (for non-cases).…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…In a previous study from our group, we confirmed the high positive predictive value of this diagnostic code in our EMR, consistent with published literature 24, 2628 . Our main predictor of interest was undergoing a colonoscopy within 36 months prior to the first date of CRC diagnosis (for cases) or end of follow-up (for non-cases).…”
Section: Methodssupporting
confidence: 92%
“…Among patients who did not have CRC, we required at least 3 years of care in our system, no colectomy during this period, and counted only colonoscopies occurring within 3 years of the date of last visit in our system to ensure a similar time frame of reference as the CRC group. Mortality was determined by linkage to the social security death index with updates every month as described previously 24 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, patients with pancreatic cancer are more likely to be Helicobacter pylori positive (OR 2.78) 18. Patients with inflammatory bowel disease (IBD)—both Crohn's disease and ulcerative colitis—have an increased lifetime risk of pancreatic cancer (OR 11.22) 19. This risk is further increased in patients with IBD with associated primary sclerosing cholangitis 19.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Patients with inflammatory bowel disease (IBD)—both Crohn's disease and ulcerative colitis—have an increased lifetime risk of pancreatic cancer (OR 11.22) 19. This risk is further increased in patients with IBD with associated primary sclerosing cholangitis 19. Furthermore, patients who have hepatitis B have an increased risk of pancreatic cancer (OR 1.50)20 and hepatitis C virus may also cause an increased risk (HR 1.6)21 although the association is less clear.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Various malignancies have been reported to be associated with PSC such as cholangiocellular (CCA) [9,10] , colorectal [10] , gallbladder [11] , pancreatic [8,12] , and hepatocellular cancer [13] , although the association of later 2 may not be strong and has been discussed controversially [14,15] . CCA represents the most frequent malignancy and is the mostly feared malignant complication of PSC.…”
Section: Introductionmentioning
confidence: 99%